2017
DOI: 10.20944/preprints201703.0048.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Understanding and Attitudes towards Meat Chicken Production and Relations to Consumption

Abstract: Simple Summary: Public knowledge of meat chicken production and how it influences attitudes to birds' welfare and consumer behaviour is poorly understood. We therefore conducted a survey of the public in SE Queensland, Australia, from which we determined that industry knowledge was limited. Where it existed, it related to an empathetic attitude towards chicken welfare and an increase in chicken consumption. This suggests that consumers who eat more chicken believe that they should understand the systems of pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Based on these results, the authors concluded that respondents' perceptions of animal emotions, including pain, may not be predictive of their preference for the welfare in pig or fish farming (28). Previous research examining Australian consumer attitudes toward and knowledge of chicken production reported a relationship between empathy toward chickens and lack of knowledge; respondents with the lowest knowledge scores were accepting of inadequate stunning of chickens during slaughter (29). Other research has also confirmed the association between lack of knowledge and lack of concern for animals (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the authors concluded that respondents' perceptions of animal emotions, including pain, may not be predictive of their preference for the welfare in pig or fish farming (28). Previous research examining Australian consumer attitudes toward and knowledge of chicken production reported a relationship between empathy toward chickens and lack of knowledge; respondents with the lowest knowledge scores were accepting of inadequate stunning of chickens during slaughter (29). Other research has also confirmed the association between lack of knowledge and lack of concern for animals (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…It is understood that as the number of family members increases, the purchasing decision was affected more (Table 2). Beyond all that, it is concluded that the public's knowledge has an important connection to their attitudes and consumption of chicken meat (Erian and Phillips, 2017).…”
Section: Responds Of Questionnairesmentioning
confidence: 99%
“…In conventional broiler production systems, birds are reared in strictly controlled indoor conditions ( Lima and Nääs, 2005 ). Increased public concern of animal welfare in those systems ( Marchewka et al, 2013 ), including decreased ability of the birds to express natural behaviors, has increased consumers' demand for meat from poultry reared in less intense systems ( Erian and Phillips, 2017 ). Those systems are characterized by longer production cycles, where the chickens from slow-growing breeds or hybrids may develop sexual dimorphism, including adult comb size, plumage and beak coloration.…”
Section: Introductionmentioning
confidence: 99%